Antecedents of members retention in fitness: study of Fitness Clubs in Portugal - Gonçalves, Celina (2019)
The objective of the present study is to understand the members retention antecedents on fitness clubs in Portugal, in the last five years.The fitness market in Portugal, although not exponentially, continues to grow (IHRSA, 2017). This phenomenon, which was expected to be positive for the market, also increased competition between fitness clubs. As a result, they had to adapt to the changes while at the same time try to keep their members as long as possible - menbers retention.